Application of Artificial Neural Networks for Maximum Power Point Tracking of Photovoltaic Panels - Vasarevicius, D.; Martavicius, R.; Pikutis, M. (Elektronika ir Elektrotechnika, 2012)
Maximum power point tracking technique for PV panels with support of online learning artificial neural network is offered. Mathematical model of the system is implemented in Matlab/Simulink environment. Maximum power point tracking is performed using IncCond algorithm and radial basis function artificial neural network. Several criteria for estimation of system performance were derived. It is shown that ANN can increase overall system efficiency by 10%. DOI: http://dx.doi.org/10.5755/j01.eee.18.10.3065